ASSESSMENT OF PREFERENCE LEVELS FOR STICK CRACKERS WITH ADDED SPINACH (AMARANTHUS SPP) AND SEA URCHIN GONADS (DIADEMA SETOSUM) - Muchtar, Febriana (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Crackers are food liked by children and adults that can be produced in various shapes. Crackers are primarily made from starch and additional ingredients that can enhance the flavor and nutritional value. This research was performed to analyze panelists' preference for stick crackers added with spinach (Amaranthus spp) and sea urchin gonads (Diadema setosum). In this experimental research, the preferences of 15 panelists were assessed through an organoleptic test, specifically a hedonic test based on several parameters; color, aroma, taste, and crispiness of the stick crackers. Data from the preference test were collected and categorized based on a hedonic scale: 1 = dislike very much, 2 = dislike, 3 = neither like nor dislike, 4 = like, and 5 = like extremely. The results indicated that the average preference scores were 4.2 for color (like), 4.1 for aroma (like), 4.3 for taste (like), and 4.6 for crispiness (like extremely). Overall, panelists expressed a favorable opinion regarding the color, aroma, taste, and crispiness of the stick crackers. These findings suggest a positive reception of the enhanced product. It is advisable to conduct further nutritional analysis of the stick crackers incorporating spinach and sea urchin gonads to assess their nutritional benefits.